Strategi Komunikasi Dakwah Lembaga Zakat dalam Mendukung Pembangunan Ekonomi Berbasis Pemberdayaan Umat - Umar, Umar; Amelinda, Ria; Retno Cristiyan Dewi, Evi (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2025)
This study aims to analyze the strategic position of the Zakat Institution in Palopo City in response to internal and external dynamics using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis approach. A mixed-methods strategy—combining quantitative and qualitative techniques—was applied, with data collected through questionnaires and interviews. The collected data were processed using a weighted score summation method to evaluate the organization's strengths, weaknesses, opportunities, and threats, thereby determining its strategic positioning within the SWOT matrix. The results indicate that the Zakat Institution of Palopo City occupies an aggressive strategy position, suggesting the organization holds strong internal capabilities and substantial external opportunities for growth. This strategic placement reflects the institution's potential to expand its reach and enhance the effectiveness of both zakat collection and distribution. The findings of this study provide a strategic direction for the institution to foster innovation, particularly through the adoption of digital technologies and the strengthening of zakat-based economic empowerment programs, in order to promote sustainable community welfare.